CHANGES IN CLINICAL AND HEMATOLOGICAL STATUSES IN THE CHILEAN WHITES OF DEGU FOR DIABETES - Lokes-Krupka, T.; Tsvilichovsky, M.; Kravchenko, S.; Burda, T. (Scientific Progress & Innovations, 2022)
The article presents the results of the analysis of four Degu squirrels (Octodon degus) patients with diabetes. The main goal of the conducted research was to investigate the clinical and hematological indicators of the pathology. Significant violations of conditions of maintenance and diet were established. In turn, this led to the development of pathology. In the course of clinical studies, suppression of the general clinical condition was found in 100 % of animals. Classic polyuria and polydipsia were characteristic manifestations of diabetes in Degu squirrels. These clinical signs are evidence of the development of intoxication and ketoacidosis in animals with pathology. An important element of the clinical manifestation is also the development of visual disturbances. In the most severe case, the development of cataract was registered. Most of the animals (75 %) were overweight, and the squirrel with cataracts lost weight. With the determination of hematological indicators of patients with diabetes mellitus, significant blood clotting was revealed. Presumably, this happened as a result of the development of intoxication in animals. This is evidenced by an increase in the number of erythrocytes and hemoglobin content by 27.8 and 30.1 % (p≤0.01) compared to the control group of animals. The presence of an inflammatory process was also recorded in sick animals as a result of hematological studies. This result was confirmed by an increase in the number of leukocytes by 62.7 % (p≤0.01) compared to clinically healthy animals. Since the metabolism of carbohydrates undergoes significant changes in animals with diabetes, it is necessary to determine the glucose content in the blood. It should be noted the additional need to conduct a test for glucose tolerance in Degu protein for diabetes. That is, determining the content of the indicator before and after feed consumption. As a result of the research, a significant difference was found in the Degu protein values of the control and experimental groups. In particular, animals with diabetes have a significantly higher level of glucose even on an empty stomach (by 3.7 times) compared to clinically healthy animals. After feeding a portion of fodder, the protein of the control group did not significantly change the glucose index, on the other hand, the protein of the experimental group increased by 28.0% compared to the fasting indicator. In this way, it is possible to establish a significant violation of carbohydrate metabolism in the Degu protein of patients with diabetes.